Association of common genetic variants with brain microbleeds: A genome-wide association study. (15th December 2020) - Knol, Maria J.; Lu, Dongwei; Traylor, Matthew; Adams, Hieab H.H.; Romero, José Rafael J.; Smith, Albert V.; Fornage, Myriam; Hofer, Edith; Liu, Junfeng; Hostettler, Isabel C.; Luciano, Michelle; Trompet, Stella; et al.
Abstract : Objective: To identify common genetic variants associated with the presence of brain microbleeds (BMBs). Methods: We performed genome-wide association studies in 11 population-based cohort studies and 3 case–control or case-only stroke cohorts. Genotypes were imputed to the Haplotype Reference Consortium or 1000 Genomes reference panel. BMBs were rated on susceptibility-weighted or T2*-weighted gradient echo MRI sequences, and further classified as lobar or mixed (including strictly deep and infratentorial, possibly with lobar BMB). In a subset, we assessed the effects of APOE ε2 and ε4 alleles on BMB counts. We also related previously identified cerebral small vessel disease variants to BMBs. Results: BMBs were detected in 3, 556 of the 25, 862 participants, of which 2, 179 were strictly lobar and 1, 293 mixed. One locus in the APOE region reached genome-wide significance for its association with BMB (lead single nucleotide polymorphism rs769449; odds ratio [OR]any BMB [95% confidence interval (CI)] 1.33 [1.21–1.45]; p = 2.5 × 10 −10 ). APOE ε4 alleles were associated with strictly lobar (OR [95% CI] 1.34 [1.19–1.50]; p = 1.0 × 10 −6 ) but not with mixed BMB counts (OR [95% CI] 1.04 [0.86–1.25]; p = 0.68). APOE ε2 alleles did not show associations with BMB counts. Variants previously related to deep intracerebral hemorrhage and lacunar stroke, and a risk score of cerebral white matter hyperintensity variants, were associated with BMB. Conclusions: Genetic variants in the APOE region are associated with the presence of BMB, most likely due to the APOE ε4 allele count related to a higher number of strictly lobar BMBs. Genetic predisposition to small vessel disease confers risk of BMB, indicating genetic overlap with other cerebral small vessel disease markers.